Is Bortezomib a Rare Cause of Acute Pancreatitis? - Solakoglu, Tevfik; Akar, Mustafa; Aktan Kosker, Tugba; Buyukasik, Semnur; Ersoy, Osman (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: Proteasome inhibitor bortezomib bound to an assembled yeast proteasome core (PDB ID 2F16). (From Wikimedia Commons).